Program Pemberdayaan Keluarga Dhuafa Mendirikan Warung Jajanan Untuk Ibu Kamilia Warga Depok - M. Adrian Dahlan Brahim; M. Bagas Kurniawan; Faedhal Amjad Nawaf; Mulkan Habibi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Empowering poor families is an important effort to improve the economic welfare of underprivileged communities. In this context, assistance to set up a snack shop for Mrs. Kamilia aims to provide concrete support for her family's economy. Through the Participatory Action Research (PAR) method, this program involves steps such as identifying poor families, raising funds, and handing over the business capital needed to set up a stall. This program not only provides financial assistance, but also equips Mrs. Kamilia with the necessary skills to run a business. With the existence of a snack stall, it is hoped that Mrs. Kamilia can increase family income, meet daily needs, and provide a better education for her children. The results of this program show the potential for success in overcoming poverty and increasing the economic independence of poor families, so that it can become a model of sustainable empowerment in society.